Peran Guru dalam Menumbuhkan Rasa Empati Pada Siswa Sekolah Dasar dengan Metode Role Playing - Lusiani, Susi (Journal of Innovation in Teaching and Instructional Media, 2025)
This research aims to reveal the role of teachers in fostering a sense of empathy in elementary school students. Through literature studies and case analysis, this research highlights that teachers have a crucial role in forming empathetic characters in students. Teachers are not only teachers of academic material, but also as models and facilitators in developing students’ social-emotional abilities. This research found that teachers can foster empathy through various strategies, such as creating an inclusive learning environment providing examples of empathetic behavior, using learning methods that actively involve students, and encouraging positive social interactions. It is hoped that the results of this research can contribute to educators in designing effective educational programs to develop empathetic character in students. Empathy is an important character value that needs to be instilled in children from an early age. This research aims to identify effective methods that teachers can use to foster a sense of empathy in elementary school students. Through literature studies and analysis of best practices, this research concludes that several methods that have proven effective include: the use of stories and fairy tales, role-playing, group discussions, and social activities. This research also highlights the importance of consistency in the application of these methods in order to produce optimal results.